CASE REPORT: LIVER FAILURE AS A DEBUT OF AUTOIMMUNE HEPATITIS TRIGGERED BY DENGUE VIRUS IN A PREGNANT WOMAN - Sato-Espinoza, Karina (2024)
Autoimmune hepatitis (AIH) is a complex condition with unclear origins, involving genetic susceptibility and environmental triggers that lead to immune system dysfunction. We report a case of a pregnant woman from a mosquito-borne disease-endemic area who presented jaundice, abdominal pain, and pruritus, complicated by acute liver failure. Immunological markers showed AIH triggered by dengue virus infection, which was confirmed by a positive IgM test. Treatment with supportive care followed by steroids and azathioprine resulted in favorable outcomes, averting the need for a liver transplant. Although AIH can be triggered by viruses, the role of dengue in its pathogenesis remains poorly understood. Regular clinical monitoring is vital for managing AIH, particularly during pregnancy, due to variable immune status and treatment responses. Further research is necessary to understand the link between dengue infection and AIH. Individualized treatment strategies are crucial, especially during pregnancy, in order to ensure favorable outcomes.